2018
DOI: 10.1186/s12864-018-4472-9
|View full text |Cite
|
Sign up to set email alerts
|

On Burkholderiales order microorganisms and cystic fibrosis in Russia

Abstract: BackgroundMicrobes infecting cystic fibrosis patients’ respiratory tract are important in determining patients’ functional status. Representatives of Burkholderiales order are the most dangerous. The goal of our investigation was to reveal the diversity of Burkholderiales, define of their proportion in the microbiome of various parts of respiratory tract and determine the pathogenicity of the main representatives.ResultsIn more than 500 cystic fibrosis patients, representing all Federal Regions of Russia, 34.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 60 publications
0
8
0
2
Order By: Relevance
“…S2). The most interesting finding was an increase in Burkholderiales, an order of pathogenic bacteria commonly found in hospital-borne infections, in the colon of MSD/sham-irradiated mice, while the levels of Burkholderiales in the colon of MAD/sham irradiated was mice was negligible (69). Furthermore, only minor increases in Burkholderiales were observed in the colon of MAD mice exposed to 3-Gy TBI, whereas more robust increases were observed in 8.5-GyϩMAD and 3-and 8.5-GyϩMSD mice, the treatment regimens strongly associated with severe RIGIS and mortality (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…S2). The most interesting finding was an increase in Burkholderiales, an order of pathogenic bacteria commonly found in hospital-borne infections, in the colon of MSD/sham-irradiated mice, while the levels of Burkholderiales in the colon of MAD/sham irradiated was mice was negligible (69). Furthermore, only minor increases in Burkholderiales were observed in the colon of MAD mice exposed to 3-Gy TBI, whereas more robust increases were observed in 8.5-GyϩMAD and 3-and 8.5-GyϩMSD mice, the treatment regimens strongly associated with severe RIGIS and mortality (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…We also found the order Burkholderiales to be more significantly enriched in the NiO NPs-exposed groups based on LEfSe analysis at 1 day after instillation. Burkholderiales are clinically associated with the exacerbation of patients with cystic fibrosis and abundantly found in patients with lung transplantation [ 44 , 48 , 49 ]. Previous studies have shown that burkholdeira spp., included in the order Burkholderiales , exert proinflammatory effects on the lung by inducing respiratory epithelial cells to secrete cytokines such as IL-1β, IL-6, IL-8, TNF-α, MCP-1, and chemokine ligand 20 (CCL20) in humans [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ziganshina and colleagues (2016) found that the order Burkholderiales and the genus Curvibacter were elevated in patients' atherosclerotic plaque samples [15]. Voronina et al showed that Burkholderiales and other members of Ralstonia and Propionibacterium represented the most elevated taxa within atherosclerotic plaques [16]. Some bacteria founded in plaques were also associated with several clinical traits, such as alanine aminotransferase, total cholesterol, and fibrinogen levels [18].…”
Section: Gut Dysbiosis In Acvdmentioning
confidence: 99%